Measuring clicker impact on student perceptions of course and instructor. (2017) - Stevens, David P.; Fontenot, Gwen
Recent research has shown that students have positive opinions regarding the use of remote response devices ('RRD's), commonly known as 'clickers', in the classroom. Studies indicate that clickers are effective, help students engage, and improve the overall learning process. This research focuses on measuring the size of the impact of clickers, via the effect size index, on student perceptions of the instructor and course. Results indicate that student opinions of clickers are definitely related to student opinions about course and instructor. That is, the two concepts are not independent. Furthermore, the use of clickers has numerous small, medium, and large effects on various student perceptions about the instructor and the course. These results can be generalised to other studies via the effect size index and its standardised measurement scale. Some demographic differences in perceptions about clickers are also discussed.